Strategie sieci i łańcuchów dostaw - Ciesielski, Marek (Network Strategies and Supply Chain Strategies, 2005)
This is very important to distinguish ideas of supply chains and supply networks. Supply chains should be analyzed in the context of industrial networks and internationalization processes. To understand functionality of networks and supply chains it's worth research relationships - competition, cooperation and control. Paradigm of network strategies and supply chains strategies can be given by using module approach, models of firms profit and model of firms activity. There is a crucial problem how to research relationships between supply chain strategies and supply networks strategies.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1078, s. 43-49